2012
DOI: 10.1002/hed.22940
|View full text |Cite
|
Sign up to set email alerts
|

Hyalinizing clear cell adenocarcinoma of the oropharynx

Abstract: Immunohistochemical staining is essential for narrowing the differential diagnosis of these lesions. Treatment is controversial but usually consists of wide local excision and possibly a neck dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
2
8
0
Order By: Relevance
“…2,19,20 Recent cases of CCA have been documented in all regions of the head and neck. 1-8,14-17 Our findings corroborated these data. Although a great proportion of tumors presented in the major salivary glands (37%) in our study, most tumors arose from other regions in the head and neck, particularly in the oral cavity and pharynx.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…2,19,20 Recent cases of CCA have been documented in all regions of the head and neck. 1-8,14-17 Our findings corroborated these data. Although a great proportion of tumors presented in the major salivary glands (37%) in our study, most tumors arose from other regions in the head and neck, particularly in the oral cavity and pharynx.…”
Section: Discussionsupporting
confidence: 89%
“…Currently, otolaryngologists' understanding of CCA is primarily inferred from retrospective case series. [1][2][3][4][5][6][7][8] The use of the SEER database in our study allows for the analysis of demographic data and outcomes of rare malignancies such as CCA with greater statistical power. To our knowledge, this study represents one of the largest population-based analyses of CCA.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature revealed 130 cases of HCCC among 48 articles . We did exclude a number of articles that have been reported by others to represent HCCC but, in our view, did not provide sufficient histologic description to confirm the diagnosis .…”
Section: Resultsmentioning
confidence: 98%
“…The main distinctive microscopic feature of CCC is the presence of round to polygonal epithelial cells with a clear cytoplasm rich in glycogen, organized in trabeculae, cords, or solid nests surrounded by an abundant hyalinizing fibrocollagenous stroma. 2,3,[5][6][7][8][9][10] Clear cells can be found in a variety of salivary gland tumors, including benign tumors such as clear cell oncocytoma and clear cell myoepithelioma, malignant tumors such as mucoepidermoid carcinoma, epithelialmyoepithelial carcinoma, myoepithelial carcinoma, and acinic cell carcinoma, and some nonsalivary gland tumors such as some odontogenic carcinomas and metastatic renal cell carcinoma. 3,[5][6][7]9,11 The clear cytoplasm has been shown to contain abundant glycogen by PAS staining.…”
Section: Discussionmentioning
confidence: 99%
“…2,15 We summarize 22 cases of CCC occurring at the base of the tongue that have been published in case reports or series reports in the English literature since 1994 (Table 1). 2,3,[5][6][7][8][9][10][12][13][14][15][16][20][21][22][23] The clinical characteristics of all 23 cases, including our case, are examined. The mean age at diagnosis was 58.0 years (range, 32-81 years).…”
Section: Discussionmentioning
confidence: 99%